2006
DOI: 10.4103/0255-0857.25179
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatisantigen detection in pregnancy and its verification by antibody blocking assay

Abstract: Purpose: To detect the prevalence of genital infection caused by Chlamydia trachomatis in pregnant women and also to confirm the positive results using blocking antibody assay. Methods: Endocervical specimens were collected from 200 symptomatic and asymptomatic pregnant women attending the ANC OPD at M P Shah Medical College, Jamnagar. The samples were tested for presence of Chlamydia trachomatis antigen using the monoclonal antibody. Blocking antibody assay was used to further verify the positive results. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…[20] Similarly, in the present study, 25% of women with a past history of abortion were positive for C. trachomatis antigen compared to 6.7% of those without such a history.…”
Section: Discussionsupporting
confidence: 78%
“…[20] Similarly, in the present study, 25% of women with a past history of abortion were positive for C. trachomatis antigen compared to 6.7% of those without such a history.…”
Section: Discussionsupporting
confidence: 78%
“…In this study all 37 positive specimens in EIA/MOMP PCR were verified by using nested-PCR and these samples were regarded as true positive, thus the specificity of the EIA and MOMP PCR was 100%. There are some studies that reported false positive results and less specificity for antigen-EIA, indicating the need for verification of positive results by other methods such as DNA amplification ( 16 , 17 ). The variable performance of EIA for detection of C.trachomatis might be due to patient characteristics such as gender and specimen type ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…They found that the ELISA sensitivity was (56.25%) and specificity was (64.81%) and they said that the reevaluation of ELISA depending upon multiple tests as gold standard might increase its sensitivity and specificity [8]. Another study found that the ELISA method has a specificity of 94.8% and verification of positive results can further improve the specificity of this test [9]. PCR procedure also could be suitable for the confirmation of ELISA results, as it has a high concordance rate compared to the rapid test [10].…”
Section: Introductionmentioning
confidence: 99%